DAMPAK PENERAPAN SUCRE TERHADAP PEREKONOMIAN VENEZUELA - Ashry Sallatu (WANUA : Jurnal Hubungan Internasional, 2015)
This article describes the effective application of Sucre, as Latin American regional currencies in ALBA, and its impact on the Venezuelan economy. This study uses primary data collected by interviews and secondary data gathered by studying document obtained from the official website of ALBA, financial institutions in Latin American countries as well as website for analysis about Latin America. The results showed that the presence of Sucre on the economy of Venezuela is less effective at improving economy of Venezuela. This is caused partly because ALBA is ineffective in promoting Sucre to all its member states and strong counter-opinions made by United States towards ALBA.